2012
DOI: 10.1080/0972060x.2012.10644126
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Essential Oil ofTecurium mascatenses BoisGrown in Oman

Abstract: Tecurium is a plant which belongs to the family Lamiaceae (Labiataea). This study was conducted in order to investigate the phytochemical composition of the leaves of Tuecrium mascatenses grown in Oman. The volume of the isolated oil was 1.2 ml 0.5 % w/w. Thirty two compounds were detected. The main constituents were limonene (17.2 %), linalool (12.4 %), α-pinene (10.1 %), β-eudesmol (10.1 %), unknown (7.6 %), linalyl acetate (4.3 %) bergamotene (4.3 %), β-pinene(3.5 %) and β-selinene (2.5 %).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
2
1
Order By: Relevance
“…The major constituents were Limonene (17.2%), Linalool (12.4%), α-pinene (10.1%), and β-Eudesmol (10.1%) (Al Oraimiet al, 2012). Our result also showed additional chemical constituents which were not reported by using hydrodistillation method used [1]. Six compounds such as Z-β-ocimene (0.08%), Pinocarveol (0.18%), Myrtenal (0.14%), trans-Carveol (0.21%), Nerol (0.15%), and Neryl acetate (1.19%) were observed in our study but not reported through hydrodistillation method.…”
Section: Essential Oil Compositioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The major constituents were Limonene (17.2%), Linalool (12.4%), α-pinene (10.1%), and β-Eudesmol (10.1%) (Al Oraimiet al, 2012). Our result also showed additional chemical constituents which were not reported by using hydrodistillation method used [1]. Six compounds such as Z-β-ocimene (0.08%), Pinocarveol (0.18%), Myrtenal (0.14%), trans-Carveol (0.21%), Nerol (0.15%), and Neryl acetate (1.19%) were observed in our study but not reported through hydrodistillation method.…”
Section: Essential Oil Compositioncontrasting
confidence: 56%
“…Essential oil of T. muscatense, extracted through an apparatus NEOS (New Essential Oil System), was analyzed by GC-MS and identified 24 chemical constituents (88.14%) while eleven unknown compounds were also present with 11.86% of the chemical composition ( Table 3) [1]. The study identified 22 compounds (78.4%) in addition to ten unknown compounds (21.6%).…”
Section: Essential Oil Compositionmentioning
confidence: 93%
See 1 more Smart Citation